ONLINE LEARNING AND ITS IMPACTS ON TEACHERSâ€™ WORKLOADS - Nurohmat Nurohmat; Adrian Ingratubun; Dian Suminta Suria Putra (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
The outbreak of the coronavirus, especially in Indonesia, has caused the teaching and learning process to change completely. The face-to-face teaching and learning process turns into an online teaching and learning process. Teachers and students are required to be ready for implementation. Teachers must change their instructions online so that teaching and learning can continue. This creates new challenges and workloads, especially for teachers who are just starting the online teaching process. The purpose of this study was to determine whether online learning increases the workload on teachers physically, mentally, and financially. The method used was a quantitative method and the instrument used was a questionnaire that is distributed online. The samples of this research were teachers who teach at private senior vocational schools in West Jakarta. Based on the data obtained, it can be seen that the application of online learning increases the workload on teachers physically, mentally, and financially.Â  Keywords: Online, Learning, Teachers, WorkloadsÂ